1999
DOI: 10.1111/j.2042-3306.1999.tb05166.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐sectional study of gastric ulcers of the squamous mucosa in Thoroughbred racehorses

Abstract: †California Veterinary Diagnostic Laboratory Service, California 95616, California 91024, USA. Summary Although gastric ulcers have been identified relatively frequently in racing Thoroughbreds, there have been no large scale studies to determine their effect on health and performance. Two hundred and two Thoroughbred horses in active race training were selected by the attending veterinarians for gastro‐endoscopic examination. Images of the stomach mucosa were stored in a digitised format for subsequent evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
113
2
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(128 citation statements)
references
References 13 publications
9
113
2
4
Order By: Relevance
“…Gastric ulceration affects between 53 to 90% of adult horses and has been associated with colic, weight loss, and decreased performance (38,61). Many (81%) outwardly healthy Thoroughbreds in race training also have ulcers (61).…”
mentioning
confidence: 99%
“…Gastric ulceration affects between 53 to 90% of adult horses and has been associated with colic, weight loss, and decreased performance (38,61). Many (81%) outwardly healthy Thoroughbreds in race training also have ulcers (61).…”
mentioning
confidence: 99%
“…7 Entwicklung der Befunde am Pylorus bei den Fohlen der V2-Kontrollgruppe (n=20) und der V2-Pulver (n=20) des zweiten Versuchsabschnitts (Omeprazol-Pulver) von Tag 0 bis Tag 15 nach dem Absetzen Development of gastroscopic findings of the pyloric region for the foals of both groups between day 0 and day 15 after weaning ray (1995) ist es für eine Spontanheilung von Magengeschwüren bei Sportpferden essentiell, die Tiere in eine stressfreie Umgebung zu verbringen. Auch Jensen (1996) (Murray 1995, Vatistas et al 1999b (Stolte 1991), lässt sich aber bisher auf das Pferd nicht übertragen, da zwar der Nachweis von DNA-Sequenzen von H. pylori im Magen von Vollblutpferden mit Magenläsionen gelang, nicht aber der Nachweis von teilungsfähigen Keimen (Contreras et al 2007). …”
Section: Tabunclassified
“…On the other hand, necropsy revealed multifocal gastric ulcers. Sports horses, such as performance and racehorses, have a high prevalence and severity of gastric ulcers (Hammond et al 1986;Murray et al 1989Vatistas et al 1999b;Pellegrini, 2005;Jonsson & Egenvall 2006;Orsini et al, 2009). A study conducted by Pellegrini (2005) showed that almost all performance horses have some kind of ulcer and that at least 60% of them have colonic ulcers.…”
Section: Gastric Ulcersmentioning
confidence: 99%